Differences in Regional Diagnostic Strategies and in Intended Versus Actual First-Line Treatment of Patients With Advanced Ovarian Cancer in Denmark. Issue 7 (1st September 2014) - Fagö-Olsen, Carsten Lindberg; Ottesen, Bent; Kehlet, Henrik; Antonsen, Sofie Leisby; Christensen, Ib Jarle; Markauskas, Algirdas; Mosgaard, Berit Jul; Ottosen, Christian; Sogaard, Charlotte Hasselholt; Hoegdall, Claus
Abstract : Background: Triage of patients with ovarian cancer to primary debulking surgery (PDS) or neoadjuvant chemotherapy (NACT) is challenging. In Denmark, the use of NACT has increased, but substantial differences in the use of NACT or PDS exist among centers. We aimed to characterize the differences between intended and actual first-line treatments in addition to the differences in the triage process among the centers and to evaluate the different diagnostic modalities and the clinical aspects' influence in the triage process. Materials and Methods: From 4 centers, forms containing data about the diagnostic process and intended treatment were prospectively collected and merged with data from the Danish Gynecological Cancer Database and medical records. Results: Of the 671 completed forms, 540 patients had stage IIIC or IV epithelial ovarian cancer. Of the 238 (44%) referred to PDS, 91% received PDS and 4% never had debulking surgery. Of the 288 patients (53%) referred to NACT, 44% were never debulked. Fourteen patients (3%) were referred to palliative treatment. The use of different imaging modalities, diagnostic laparoscopy, and laparotomy varied significantly among the centers. Diagnostic surgical procedures were considered to be most influential in the triage process. Regardless of the intended first-line treatment or center, the tumor size and dissemination was the most influential clinical aspect. Conclusions: In Denmark, substantial differences exist between intended and actual first-line treatments as well as in the diagnostic process and use of NACT, calling for further discussion on diagnostic strategy and therapeutically approach for patients with advanced ovarian cancer.